Fractional Flow Reserve in Choosing the Tactics of Interventional Treatment of Multilevel Coronary Artery Lesions - Gavrylyshyn, Andrii Yu.; Salo, Sergii V.; Levchyshyna, Olena V.; Logutov, Andrii K.; Lazoryshynets, Vasyl V. (Ukrainian Journal of Cardiovascular Surgery, 2021)
When choosing tactics for the treatment of patients with stable coronary artery disease, invasive coronary angiography remains the gold standard for diagnosis and is a crucial method in choosing tactics and volume of revascularization. However, in the presence of borderline (>50-70%), multilevel lesions of the coronary artery, there is a need for additional assessment of the physiological significance of each stenosis. The aim. To develop an algorithm to optimize the use of fractional flow reserve (FFR) measurement in interventional treatment of borderline (>50-70%), multilevel lesions of coronary arteries, to show the safety of “functional revascula rization” in comparison with traditional angiography. Materials and methods. The study included 32 patients who were treated at the National Amosov Institute of Cardiovascular Surgery in the period from 2017 to 2021 (the vast majority were men – 25 patients (67%) and 7 (33%) women) aged 60.3±8.3 years who had >50-75% multilevel lesions of one of the main coronary arteries according to selective invasive coronary angiography. The patients were divided into two groups: 1) Angiographic group (n = 17, 53%), where the volume and tactics of revascularization were determined only by angiography (maximum complete anatomical revascularization); 2) Functional group (n=15, 47%) (combination of angiography data and FFR measurement, the so-called “functional revascularization”). Conclusions. An effective and safe algorithm for measuring FFR in multilevel lesions (reducing the number of implanted stents) is shown.